3.(ii) Factorise the following using appropriate identities:

    (ii)    4y^2 - 4y + 1

Answers (1)

We can rewrite 4y^2 - 4y + 1 as 

\Rightarrow 4y^2 - 4y + 1=(2y)^2-2\times2y\times 1+(1)^2

Using identity  \Rightarrow (a-b)^2 = (a)^2-2\times a\times b +(b)^2

Here, a= 2y \ \ and \ \ b = 1

Therefore,

4y^2 - 4y + 1=(2y-1)^2=(2y-1)(2y-1)

Preparation Products

Knockout KCET 2021

An exhaustive E-learning program for the complete preparation of KCET exam..

₹ 4999/- ₹ 2999/-
Buy Now
Knockout KCET JEE Main 2021

It is an exhaustive preparation module made exclusively for cracking JEE & KCET.

₹ 27999/- ₹ 16999/-
Buy Now
Knockout NEET Sept 2020

An exhaustive E-learning program for the complete preparation of NEET..

₹ 15999/- ₹ 6999/-
Buy Now
Rank Booster NEET 2020

This course will help student to be better prepared and study in the right direction for NEET..

₹ 9999/- ₹ 4999/-
Buy Now
Knockout JEE Main Sept 2020

An exhaustive E-learning program for the complete preparation of JEE Main..

₹ 12999/- ₹ 6999/-
Buy Now
Exams
Articles
Questions